Grade 3 trastuzumab-induced neutropenia in breast cancer patient. (April 2014) - Ghani, Ehab A; Kerr, Ian; Dada, Reyad
Trastuzumab, a humanized monoclonal antibody, is widely considered the most important development in the treatment of breast cancer since tamoxifen. Previous studies have found trastuzumab reduces the risk of relapse in breast cancer patients significantly when given in the adjuvant setting. As a targeted therapy, it has lesser side effects in comparison with conventional chemotherapy. However, the administration of this agent can cause serious side effects. We report on a 45-year-old woman with breast cancer, positive for human epidermal growth factor receptor 2 by immunohistochemistry score 3+, who was treated in an adjuvant setting with trastuzumab and developed severe neutropenia. Twenty seven weeks after initiation of trastuzumab, the patient developed fever, neutropenia (grade 3), and oral stomatitis (grade 4). The maintenance therapy was stopped for approximately 8 weeks. After recovery of the neutrophils, trastuzumab was restarted. Two weeks later, the patient developed the same pattern of toxicity. The situation necessitated the discontinuation of trastuzumab. Thereafter, the neutrophils normalized and the patient's condition improved. To our knowledge, this is the first case in the literature describing severe neutropenia directly related to trastuzumab during the adjuvant maintenance therapy. Clinicians should be aware of this rare side effect of trastuzumab, as stopping this agent can prevent severe complications.